Determinants of Shopee Paylater Usage Decisions with Financial Management Behavior A Moderating Variable - Widodo, Az Zahra Zain; Furqonul Haq (Journal of Islamic Economic Scholar, 2024)
In the era of modern globalization, technology is developing rapidly, marked by the presence of digital-based financial technology in people's lives. This technology, known as financial technology (fintech), presents new innovations in the financial industry in Indonesia in the form of the Paylater feature on the Shopee marketplace. This study uses a quantitative approach with a questionnaire research method with a sample of 155 respondents with all respondents specifically for Shopee Paylater service users in generation Z in DI Yogyakarta who are not yet working. The analysis method used in this study is SEM-PLS with the help of the WarpPLS 7.0 analysis tool. The results of this study indicate that partially, religiosity, income, risk perception, and lifestyle have a significant positive effect on the decision to use Shopee Paylater. Financial Management Behavior does not moderate the partial relationship between religiosity, risk perception and lifestyle on the decision to use Shopee Paylater. While Financial Management Behavior is proven to moderate the relationship between income and the decision to use Shopee Paylater.